2019
DOI: 10.1093/jac/dkz450
|View full text |Cite
|
Sign up to set email alerts
|

Tigecycline-non-susceptible hypervirulent Klebsiella pneumoniae strains in Taiwan

Abstract: Objectives Emergent antimicrobial-resistant hypervirulent Klebsiella pneumoniae (hvKp) is an important public health issue. We aimed to investigate resistance mechanisms and hypervirulent traits among tigecycline-non-susceptible (TNS) K. pneumoniae clinical strains, focusing on one hvKp strain with in vivo evolution of tigecycline resistance. Methods TNS K. pneumoniae strains causing invasive diseases in a medical centre in T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 34 publications
0
13
2
Order By: Relevance
“…This could explain why the treatment was not effective in the case. Yi-Hsiang Cheng et al identified alterations in the rmpA as a mechanism of in-vivo tigecycline resistance development in a hvKP strain [16] . And Hiroki Namikawa et al reported that RFP, which inhibits not only transcription of the rmpA gene but also capsular polysaccharide biosynthesis to reduce capsular thickness, may serve as potential anti-virulence agent for hvKP infection.…”
Section: Discussionmentioning
confidence: 99%
“…This could explain why the treatment was not effective in the case. Yi-Hsiang Cheng et al identified alterations in the rmpA as a mechanism of in-vivo tigecycline resistance development in a hvKP strain [16] . And Hiroki Namikawa et al reported that RFP, which inhibits not only transcription of the rmpA gene but also capsular polysaccharide biosynthesis to reduce capsular thickness, may serve as potential anti-virulence agent for hvKP infection.…”
Section: Discussionmentioning
confidence: 99%
“…High-level expression of efflux pump is the main mechanism of bacterial resistance to tigecycline (45). Mutation in local transcriptional repressor acrR and global transcriptional activator ramA could result in the overexpression of AcrAB efflux pump (46).…”
Section: Discussionmentioning
confidence: 99%
“…Tigecycline resistance genes included efflux pump-related genes ( acrA/B/R , oqxA/B/R , rarA , ramA/R , marA/R , soxS/R and lon ), tet genes [ tet (A), tet (X), tet (L) and tet (M)], and the ribosomal protein S10-encoding gene ( rpsJ ) [ 15 , 31 , 32 ], and colistin resistance genes were focused on LPS modification genes ( pmrA/B , phoP/Q , crrA/B , mgrB and mcr-1 ) [ 17 ]. By using CRKP-Urine1 as the reference sequence, tigecycline or colistin resistance genes were involved in the sequence analysis on the basis of the long contigs obtained by Illumina sequencing.…”
Section: Methodsmentioning
confidence: 99%